How to assess existing multi-stakeholder platforms and networks - Minh, Thai Thi; Ofosu, Abena; Melaku, Dagmawi (International Water Management Institute, 2023)
Analyzing the existing multi-stakeholder platforms, dialogues, and networks helps create an overview of all relevant stakeholders for setting up multi-stakeholder dialogues and together achieve large-scale impact with innovation scaling.